An Evaluation of On-Farm Food Loss Accounting in Life-Cycle Assessment (LCA) of Four California Specialty Crops - Winans, Kiara; Marvinney, Elias; Gillman, Anne; Spang, Edward (Frontiers in Sustainable Food Systems, 2020)
The majority of the environmental impacts associated with the agri-food supply chain occur at the production phase. Interests in using life-cycle assessment (LCA) for accounting for agri-food supply chains as well as food losses and waste (FLW) has increased in recent years. Here, for the first time, we estimate production-phase embedded resources and greenhouse gas (GHG) emissions in California specialty crops considering on-farm food losses. We use primary, survey-derived qualitative, and quantitative data and consider on-farm food loss prevention and avoided GHG emissions through two different scenarios applied in an illustrative example for processing peach at the production stage. Further, we contribute a mathematical approach for accounting for discrete, unique flows within the net flow of loss in a supply chain, in LCA. Through the detailed LCAs, we identify the hotspots for the four crops as on-farm diesel use, fertilizer application, direct water use, and electricity for irrigation pumping. Impacts from cultivation practices and the additional impacts from on-farm food losses vary significantly by crop. Including the losses in the LCAs resulted in increases in overall resource use and GHG emissions by 4–38% (percent varies depending on the crop type). We used the LCA models and a set of straightforward calculations to evaluate the environmental impacts of a prevention action (a 50% reduction in on-farm food losses) and the secondary use of end-of-life (EOL) biomass from processing peach. The results of this evaluation showed an 11% reduction in GHG emissions compared to the baseline (full harvest). In conclusion, by explicitly including the impacts of on-farm food losses in LCA, we highlight challenges and opportunities to target interventions that simultaneously reduce these losses and the associated environmental impacts in agricultural systems.